2022
DOI: 10.3390/jpm12020222
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of Patients with Gynaecological Uterine Sarcomas in a Tertiary Hospital

Abstract: Uterine sarcomas are rare and heterogeneous malignancies accounting for 1% to 3% of all gynaecological tumours. There are many histological subtypes recognised, including leiomyosarcomas, endometrial stromal sarcoma, and uterine carcinosarcoma, although the latest has been recently discarded in this group. Despite its low incidence, these types of cancer currently entail multiple challenges, either in diagnostics or clinical management, with a poor prognosis associated. The present work aimed to complete a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
(126 reference statements)
1
1
1
Order By: Relevance
“…As described in our study, 97.33% of patients received primary surgery, among who 93.15% had TH-BSO and 6.85% had a hysterectomy as their rst-line treatment within 1 month after diagnosis. This nding was in line with other studies reporting surgical treatment rates ranging from 87.6% to 98% [27]. In our research, the effect of surgery with ovarian function preservation on survival was not analyzed due to the small sample size (n=2).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…As described in our study, 97.33% of patients received primary surgery, among who 93.15% had TH-BSO and 6.85% had a hysterectomy as their rst-line treatment within 1 month after diagnosis. This nding was in line with other studies reporting surgical treatment rates ranging from 87.6% to 98% [27]. In our research, the effect of surgery with ovarian function preservation on survival was not analyzed due to the small sample size (n=2).…”
Section: Discussionsupporting
confidence: 87%
“…In our study, 26 out of 75 patients (34.67%) had recurrence, which was slightly lower than the reported recurrence rate range of 50-70% by previous studies [24][25][26]. In addition, our study showed that all relapses occurred in the pelvis, although Maria Ruiz-Minaya [27] reported multiple metastases were common.…”
Section: Discussioncontrasting
confidence: 68%
“…Several studies in the literature have reported LMS as the most common histological subtype of uterine sarcoma. 15,16 In contrary,…”
Section: Discussionmentioning
confidence: 96%